2011
DOI: 10.5137/1019-5149.jtn.3321-10.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mortality probability of preoperative MRI features in malignant astrocytomas

Abstract: AIm:The aim of the present study is to analyze the effects of the MRI features on the recurrence time and prognosis, and to emphasize the analyses of mortality risks in malignant astrocytomas. mAterIAl and methOds:The effects of preoperative MRI features on prognosis were studied for follow-up period of 45 months, from November 1999 to August 2003, on a total of 79 patients' 41 cases of total resection and 38 cases of subtotal resection diagnosed to have malignant astrocytoma subsequent to craniotomy. results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Regarding the prognostic role of tumor necrosis, there are various results among the limited numbers of survival studies in GBM. 10,19,21,24 Hammoud et al 19 found that the amount of tumor necrosis on preoperative scans was the strongest prognostic variable. This is similar to other retrospective studies 10,24 ; however, our study showed no significant association between degree of tumor necrosis and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the prognostic role of tumor necrosis, there are various results among the limited numbers of survival studies in GBM. 10,19,21,24 Hammoud et al 19 found that the amount of tumor necrosis on preoperative scans was the strongest prognostic variable. This is similar to other retrospective studies 10,24 ; however, our study showed no significant association between degree of tumor necrosis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…10,19,21,24 Hammoud et al 19 found that the amount of tumor necrosis on preoperative scans was the strongest prognostic variable. This is similar to other retrospective studies 10,24 ; however, our study showed no significant association between degree of tumor necrosis and survival. This can be attributed to differences in measurement and grading system, that is, Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…While necrosis has also typically been implicated in survival [ 50 , 51 ], other studies have not found significant associations. For example, in a study, based in part on the patients used in the present analysis, necrosis was not found to be associated with survival.…”
Section: Discussionmentioning
confidence: 99%
“…Gliosarcomas are rare neoplasms of the central nervous system, constituting 0.48% of intracranial tumors and 1.8-10% of glioblastomas [1][2][3][4][5][6][7][8][9]. They were first described in 1895 as brain neoplasms formed by glial and mesenchymal components and in 2000 the World Health Organization (WHO) classified them as a variant of glioblastomas.…”
Section: Introductionmentioning
confidence: 99%